Novel insecticidal properties of bioactive zoochemicals extracted from sea urchin Salmacis virgulata - Ramachandran Karnan; Vinayagam Ramachandran; Govindan Usha Nandhini; Bakthavatchalam Senthil; Ramalingam Shunmuga Vadivu; Marimuthu Sukumaran; Hirad Abdurahman Hajinur; Wen Zhi-Hong; Kang Sang Gu; Lo Yi-Hao (Open Chemistry)
The present investigation assessed the insecticidal potential of zoo chemicals extracted from the test (skeleton) and spines of the sea urchin Salmacis virgulata against Tribolium castaneum, Aedes aegypti, and the Sf-9 cell line through assays for in vitro acetylcholinesterase (AChE) inhibition, cytotoxicity, repellency, larvicidal activity, and in silico modeling. Gas chromatography–mass spectrometry (GC–MS) analysis of the 50% ethanolic extract identified 40 distinct zoochemicals, including four with known pesticidal properties, from the test and spines of S. virgulata. The zoo extract exhibited promising insecticidal activity, demonstrated by in vitro AChE inhibition with an IC50 of 143.41 µg/ml. Additionally, in vitro cytotoxicity was measured with an EC50 of 194.68 µg/ml, a repellent index (IR) of less than 0.80, and an LC50 for larvicidal toxicity of 153.205 µg/ml. Further statistical and computational techniques confirmed the insecticidal activity of S. virgulata test and spine 50% zoo-extract against T. castaneum and A. aegypti. The identified zoochemicals that are similarly involved in insecticidal activity on all selected insecticide molecular targets have a very strong correlation, with a range of r = 0.977–0.995. This highlights a positive correlation between the insecticide molecular target and strong evidence on zoological insecticides of S. virgulata test and spines against harmful pests through AChE enzyme inhibition, cytotoxicity, repellence, and larvae toxicity. We recommend the utilization of zoo waste from the sea urchin S. virgulata as a promising source of zoological insecticides. These bio-based pesticides offer an eco-friendly approach to pest control through their repellency and toxicity, being readily biodegradable and presenting lower environmental risks compared to synthetic pesticides.